Examining The Meaning Of The Word Uffin As A Form Of Sarcasm From The Quranic Perspective - Ihsan, Lalu Muhammad Zainul; Ridho, Abdul Rasyid; Kamis, Mohd. Sham (ZAD Al-Mufassirin, 2024)
This study discusses the interpretation uffin in the Qur'an as a form of sarcasm in response to the decline of morality ethics in social interaction between people or generations. The type of research used is analytical descriptive research with a qualitative approach, because it  is a method used to analyze the contents of the message conveyed by the verses mentioned the word uffin in it based on the interpretation of ulama. The results found that the word uffin was used in different contexts, both as a prohibition on hurting parents, as an expression of anger and disapproval, and the uffin words as denial to God, parents and those who give religious advice or the message of kindness to others. According to the ulama interpretation, uffin expresses dissatisfaction, anger, even insult, which is considered linguistically rude or full of annoyance. These results provide insight into how the word uffin is used as sarcasm in social interaction. The implications of this research emphasize the need to understand the context of the use of sarcasm in everyday life and to develop the right attitude in responding to it, in order to maintain ethical and moral harmony in social interactions.